2012
DOI: 10.1111/aogs.12011
|View full text |Cite
|
Sign up to set email alerts
|

Contraindications for external cephalic version in breech position at term: a systematic review

Abstract: The present study shows that there is no general consensus on the eligibility of patients for ECV. Therefore we propose to limit contraindications for ECV to clear empirical evidence or to those with a clear pathophysiological relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Previous caesarean section was the most common reason women were deemed ineligible for ECV with only 2.6% of women with ECV having a history of caesarean section compared to 16.6% in women with breech presentation overall. There may be a clinical perception that with a previous caesarean section there are no safe options, however, there is little evidence that caesarean section should be considered an absolute contraindication for ECV [21]. To the contrary, there is some evidence suggesting the success and associated risks of ECV in women with one previous caesarean section are similar to those in women without such history [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous caesarean section was the most common reason women were deemed ineligible for ECV with only 2.6% of women with ECV having a history of caesarean section compared to 16.6% in women with breech presentation overall. There may be a clinical perception that with a previous caesarean section there are no safe options, however, there is little evidence that caesarean section should be considered an absolute contraindication for ECV [21]. To the contrary, there is some evidence suggesting the success and associated risks of ECV in women with one previous caesarean section are similar to those in women without such history [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Nulliparity was found to be independently associated with ECV failure, as previously reported by various authors. 10,23,24 The lower success rate in nulliparous women is thought to be attributed to tenser abdominal muscle and uterus. 25 In addition, we demonstrate that anterior placenta is independently associated with ECV failure, supporting previously published data.…”
Section: Discussionmentioning
confidence: 99%
“…32 Interestingly, in a recent systematic review of the published international guidelines regarding ECV, Rosman et al found that there was no consensus or empirical evidence for the majority of cited contraindications to ECV. 33 The authors recommend that the absolute contraindications to ECV should be restricted to oligohydramnios, clinical evidence of placental abruption, maternal conditions such as severe preeclampsia or HELLP syndrome, and signs of fetal distress. 33 Thus, factors such as primiparity, obesity, advanced gestation, excessive fetal weight, or anterior placenta should not limit eligibility.…”
Section: External Cephalic Versionmentioning
confidence: 99%
“…33 The authors recommend that the absolute contraindications to ECV should be restricted to oligohydramnios, clinical evidence of placental abruption, maternal conditions such as severe preeclampsia or HELLP syndrome, and signs of fetal distress. 33 Thus, factors such as primiparity, obesity, advanced gestation, excessive fetal weight, or anterior placenta should not limit eligibility. 33 Associated factors that may improve the success of ECV include multiparity, lack of engagement, frank or complete breech, ability to palpate the fetal head, and low maternal weight.…”
Section: External Cephalic Versionmentioning
confidence: 99%
See 1 more Smart Citation